Simulation learning in pediatrics and neonatology: evaluation, recognition and stabilization of emergencies in children - O.O. Starets; N.V. Kotova; K.O. Loseva; O.V. Fedorenko (Zaslavsky O.Yu., 2018)
Background. Simulation learning is a new and very rapidly developing area of medical education. This method is especially important for the development of practical skills of emergency care for children. The purpose of the article is to discuss the implementation of the basic approaches of American Heart Association and Academic Pediatric Association training courses PEARS® and simulation learning. Materials and methods. The authors present the results of implementation of approaches to the evaluation, recognition and stabilization of emergency conditions in children using the simulation training. Results. 786 students and 158 physicians were trained in the simulation class of the department of propaedeutic pediatrics in the Odessa National Medical University. They learnt the basics approaches of the training course "Evaluation, recognition and stabilization of emergencies in pediatrics". Students and physicians noted the high efficiency of combination of theoretical material and simulation training for getting practical skills. Conclusions. It is necessary to use both the evidence based clinical protocols of emergency care and educational programs of professional associations implemented in developed countries.